The Influence of Traditional Dayak Desa Leadership Values on Community Harmony in Sekadau Regency - Adil Bertus AS; Darius Damestuteles; Fitria Elvi (Sean Institute, 2025)
This study explores the influence of traditional leadership values within the Dayak Desa community on social harmony in Sekadau Regency, West Kalimantan. Rooted in local wisdom, the leadership practices of the Dayak Desa are based on principles such as costumary justice, communal consensus, moral exemplarity, restorative conflict resolution, and collective solidarity. Using a qualitative approach, the research involved in-depth interviews and participatory observation. The findings reveal that customary leaders, such as the temenggung, play a central role in maintaining social order, resolving disputes, and upholding ethical standards. These leadership values foster a strong sense of belonging, mutual respects, and social cohesion. However, the study also highlights challlenges related to the generational gap, where younger members are becoming less engaged in traditional practices. Strategic efforts involving cultural educational and intergenerational dialogue are essential to ensure the sustainability and relevance of customary leadership values in the face of medernization. This research underscores the critical role of traditional leadership in preserving communal harmony and cultural identity.